Analysis of mineral contents of fruits of Lycium barbarum L. (Solanaceae) cultivated in Serbia - Ilić, Tijana; Kodranov, Igor; Kolašinac, Stefan; Ivanović, Nevena; Vidović, Bojana (Archives of Pharmacy, 2022)
Fruits of Lycium barbarum L. (Solanaceae), known as wolfberries or goji berries, have been long used in traditional medicine and nutrition in Asian countries. However, in recent years, they have become popular in Europe, including Serbia. However, there are limited data on the chemical composition of goji berries cultivated in our country. This study aimed to estimate and perform a comparative analysis of the mineral content of goji berries from six locations in Serbia. After microwave digestion, macro- (K, Na, P, S, Mg, Ca) and microelement (Fe, Zn, Cu, Cr, Mn, Mo) contents in analyzed samples were determined by the optical emission spectrometry with induced coupled plasma (ICP-OES). As expected, mineral concentrations varied significantly among goji berry samples from different locations (p < 0.05). In general, the decreasing orders of minerals in goji berries were: K > P > S > Na > Mg > Ca > Zn > Fe > Cu > Mn > Cr > Mo. According to the Recommended Daily Allowance (RDA) values, dried goji berries (30 g) provide a rich source of Cr and Cu, while their contribution to the daily intake of other minerals was below 15% RDA.